Digiwork: how agriculture 4.0 is changing work for farm advisers - Ruth Nettle; Julie Ingram; Margaret Ayre (Frontiers in Sustainable Food Systems)
IntroductionAdvisers are commonly involved in supporting farmers navigate the smart farming transition, however their experiences in such roles, and any changes to their working lives, has not received a great deal of empirical attention. Knowledge about these changes would enable greater anticipation of disruptions to advisory work and help support strategies to maintain and build advisory capacity. This is important for stakeholders seeking to strengthen the advisory system as part of the Agriculture 4.0 era. This paper reports on a study of advisers in the UK and Australia who work with farmers in implementing Smart Farming Technologies (SFTs), to examine the ways in which their work is changing. Changes to the work of advisers is a less explored topic within smart farming yet is an important aspect to the way the Agriculture 4.0 is unfolding.MethodWe developed a multidisciplinary framework from the literature relating to work and working life to collect and analyse data with an overarching theoretical framing of advisory practice as socio-symbolic and socio-material relations. We interviewed 22 advisers and 4 Agricultural technology (AgTech) company representatives about changes to their work as their farming clients implement SFTs.ResultsBased on qualitative analysis of the interview transcripts, and applying grounded theory techniques of constant comparison, we found a range of changes to work including: the diversity of advisory roles; integration work or the emerging ‘side office’ at the nexus of the office and the farm; demands in work duration and changes in work efficiency and effectiveness; increased workload in learning and developing new knowledge and skills and in the work of building and adapting business models fit for smart farming.DiscussionWe discuss three contributions to the understanding of changes to advisory work: the evolution in advisory roles (including bifurcation and specialisation of roles) expanded knowledge brokering and intermediary work and digiwork, or the work of integrating social, material and symbolic practices in smart farming. These changes have implications for the functioning of the advisory system which, without collective support from government or industry, will privilege technology-centric, commercial and privatised advisory efforts.